Unilateral rhinolith in an adult man: a case report (Bangladesh Journal of Medical Science, 2017)
Foreign bodies in the nose are rarely seen among adults. Rhinoliths are uncommon intranasal foreign bodies that have a very low incidence. They are often asymptomatic may be up to many years and subsequently present with nasal symptoms. We reported a case of an adult man with unilateral rhinolith, who complained of unilateral nasal blockage and foul-smelling nasal discharge. He was diagnosed with rhinolith endoscopically and successfully removed under general anaesthesia.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.448-451